Poverty, stressful life events, and coping strategies - Palomar Lever, Joaquina (The Spanish Journal of Psychology, 2008)
It was hypothesized that individuals of low socioeconomic status are exposed to a greater number of stressful events and therefore have a higher incidence of psychological disorders. However, the way they interpret, evaluate and cope with these stressful situations may either cause them to maintain, intensify or eliminate their overall stress. Past research indicates that the poorest individuals tend most frequently to falsely minimize or avoid stressful situations, which lowers the probability of resolving their problems. The objective of this study is to discover and compare the situations that have produced a high level of stress in subjects of three different socioeconomic groups over the last three months, as well as the strategies they used to cope, and their perceived effectiveness. The sample included 900 subjects of both sexes living in Mexico City. Among them, 346 were extremely poor, 260 were moderately poor and 312 were not poor. The results indicate that socioeconomic status is related to the frequency with which subjects report certain kinds of stressful situations. It was also found that non-poor subjects use problem-focused coping methods more than the other groups, while the poor use more emotionally-focused coping strategies. This article analyzes the strategies used by each group in each type of stressful situation reported.